From Waste to Energy: The Electrochemical Reduction of CO2 Using Recycled Nanostructured Catalysts - Badawy, Ibrahim (AUC Knowledge Fountain, 2023)
The reduction of carbon dioxide (CO2RR) using electrochemistry is a promising solution for the burgeoning global energy crisis. The overall vision of its implementation relies on renewable energy sources to power the reaction creating carbon neutral products and effectively closing the carbon cycle. Research in this field has come a long way since its inception in the mid-1900s. However, there remain significant hurdles and important considerations to overcome in order to reach full commercialization. Most electrocatalysts tested for CO2RR have been designed solely for maximum performance while ignoring the environmental consequences if such a material were manufactured at scale. This thesis aims to address this concern by developing an electrocatalyst that is derived from scrap alloys as an environmentally conscious material that can be easily scaled up. The thesis begins by constructing an in-house designed and manufactured reaction cell with an overall configuration that includes a gas chromatograph (GC) and a high-performance liquid chromatograph (HPLC). The work proceeds to employ scrap brass and scrap aluminum bronze alloys for use as electrocatalysts. The two types of alloys were nanostructured and tested for their activity towards CO2RR. As the Zn content increased in the sample, the brass showed improved CO production. The CO2 activity was improved further through galvanic replacement of Ag on the surface. The addition of Ag improved the selectivity of the electrocatalyst by shifting from CO to HCOOH. Density functional theory (DFT) modeling was utilized to gain insight on the selectivity improvement upon adding Ag. The d-band center of the catalyst was shifted closer to the Fermi level, indicating higher catalytic activity upon Ag addition. The aluminum bronze, on the other hand, was compared with pure copper as a benchmark catalyst. After the chemical modification via wet etching, the aluminum bronze sample demonstrated a higher selectivity towards HCOOH compared with pure copper. Various electrochemical techniques were applied to understand the origin of this shift. DFT modeling revealed that the aluminum bronze helped facilitate the binding of the CO2 molecule through its oxygen terminals rather than through the carbon atom. This orientation favors the production of HCOOH. Carbon monoxide reduction (COR) was performed in order to corroborate this finding.